The Role of Minerals in Geopolitics and Geoeconomics. Strategic Implications and Challenges for Peru - Jiménez Bernal, André (2025)
This article provides an introductory overview of the current international landscape, marked by growing competition for “critical” or “strategic” minerals in the context of the energy transition, digitalization, and global geoeconomic restructuring. In this context, the persistent and strategic role of these resources has regained central importance in the reconfiguration of supply chains and global power dynamics. Both developed and developing economies with abundant reserves have begun to implement strategies and measures to secure access and enhance the benefits derived. Based on this context, the text reviews some of the strategic challenges and implications that Peru faces as a relevant mining actor in the region, at a time when mining holds a prominent place in international agendas.